(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the key aspects of Japan’s higher education system and the possibilities of adapting them to Uzbekistan’s higher education system. The study explores Japan’s education quality, innovative teaching approaches, university-industry collaboration, and personnel training system. Recommendations for applying Japanese experience in Uzbekistan are proposed.